La place de l’espace proche dans l’évolution des programmes de géographie de l’école élémentaire française de 1977 à 2015 - Elsa Filâtre (Unité Mixte de Recherche 8504 Géographie-cités, 2020)
The article proposes to study the evolution of French geography programs in elementary school, i.e., for students aged from six to eleven, from 1977 to 2015, the date of the last published program. The purpose is to identify in this period, which saw six curriculum changes, the main themes of discourse in school geography, the points of continuity and rupture between the curricula and, in particular, the place that the curricula give to teaching with the near space environment of the students. These changes occurred in a context of epistemological renewal of French university geography that has had an impact on school geography. The corpus is analysed using lexicometry to identify, in addition to classic textual analyses, the main categories of discourse identified in geography programs. The results make it possible to grasp the proximities between past and present curricula, which place the near environment as the object of study but also provide an epistemological viewpoint on nearly 40 years of curriculum evolution.